Trypanosoma congolense: A comparison of T-cell-mediated responses in lymph nodes of trypanotolerant and trypanosusceptible cattle during primary infection - Lutje, V.; Taylor, K.A.; Kennedy, D.; Authié, Edith; Boulange, A.F.; Gettinby, George (Elsevier, 1996)
A comparison of T-cell-mediated immune responses in trypanotolerant N'Dama and susceptible Boran cattle during primary infection with tsetse-transmitted Trypanosoma congolense was conducted to assess whether different patterns of T-cell activation occurred during trypanosome infection. Proliferation and IFN-y synthesis in response to trypanosome antigens and to the mitogen Con A were measured in LNC before infection and 10 and 35 days postinfection. Phenotypic analysis of LNC was also carried out. No significant differences in the in vitro proliferation of LNC to VSG, to hsp 70/BiP, or to Con A were detected between the breeds. In contrast, IFN-y production in response to Con A was higher in Boran cattle at 35 days p.i. A reduction in the number of CD2+ and CD4+ T-cell and an increase in the percentage of B-cells, CD8+T-cells, and yo T-cells during infection in both N'Dama and Boran was revealed by cytofluorimetric analysis to lymph node cells.